Photovoltaic solar energy for the exploitation of underground water - Farfán Neyra, José Luis (2019)
The objective of the present research lies in the use of the photovoltaic solar energy in the exploitation of underground water with agricultural purposes in the basin Motupe-Olmos-La Leche, as a better alternative with respect to the traditional method of pumping water using electrogen groups or electric energy. The study zone, according with the Solar Map of Peru elaborated by the Meteorology and Hydrology National Service (SENAMHI) in agreement with the Energy and Mines Minister (MEM) has a high available daily solar radiation, whose values oscillates between 5,5 and 6,0 Kwh/m2 day. The Water National Authority (WNA) of the Agricultural Minister (AM) to 2014 reports the existence of 4339 underground water wells in the study zone, the same that it involves the localities of Motupe, Olmos, Pacora, Jayaca, Chochope, Pitipo and Salas, whose exploitation is made generally using electrogen groups (inner combustion motors, burning oil and gasoline). This report contains technical characteristic, measurements and exploitation of wells (volume of water). Taking account the available of the local solar radiation, the daily hydric demand, it is determined the technical characteristics of design of a system that let the exploit of underground water with agricultural purposes trough the use of the solar energy, promoting in this way the supporting application of the photovoltaic energy, as a clean alternative and free of emission of gases of greenhouse effect.